2022
DOI: 10.3389/fphar.2022.968256
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNAs: Potential mediators between particulate matter 2.5 and Th17/Treg immune disorder in primary membranous nephropathy

Abstract: Primary membranous nephropathy (PMN), is an autoimmune glomerular disease and the main reason of nephrotic syndrome in adults. Studies have confirmed that the incidence of PMN increases yearly and is related to fine air pollutants particulate matter 2.5 (PM2.5) exposure. These imply that PM2.5 may be associated with exposure to PMN-specific autoantigens, such as the M-type receptor for secretory phospholipase A2 (PLA2R1). Emerging evidence indicates that Th17/Treg turns to imbalance under PM2.5 exposure, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 174 publications
0
2
0
Order By: Relevance
“…Meanwhile, it causes disorder of Th1, Th2, Th17 and Treg cells in rat intestinal and kidney tissues, but without signi cant differences. The Th17/Treg cell ratio correlates with the in ammatory response and the maintenance of immune homeostasis in the body [39]. Analysis of Th17/Treg showed that DN modelling leads to an immune imbalance in the kidney and gut and consequently induces the activation and transfer of in ammatory factors, leading to increased kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it causes disorder of Th1, Th2, Th17 and Treg cells in rat intestinal and kidney tissues, but without signi cant differences. The Th17/Treg cell ratio correlates with the in ammatory response and the maintenance of immune homeostasis in the body [39]. Analysis of Th17/Treg showed that DN modelling leads to an immune imbalance in the kidney and gut and consequently induces the activation and transfer of in ammatory factors, leading to increased kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…The liver can metabolize and decompose endogenous and exogenous substances, and lipid metabolism disorders can cause fatty liver, hepatitis and other liver diseases. Epidemiological studies have shown that PM 2.5 is not only closely related to cardiopulmonary diseases, the immune system and the nervous system [14][15][16], but also related to the incidence of liver cancer. Studies have shown that PM 2.5 and its binding compounds are deposited and metabolized in the liver, which may eventually cause liver damage [17].…”
Section: Introductionmentioning
confidence: 99%